The Dark Triad Traits from a Life History Perspective in Six Countries - Jonason, Peter K.; Foster, Joshua D.; Egorova, Marina S.; Parshikova, Oksana; Csathó, Árpád; Oshio, Atsushi; Gouveia, Valdiney V. (Frontiers in Psychology, 2017)
Work on the Dark Triad traits has benefited from the use of a life history framework but is has been limited to primarily Western samples. Here we examine how the Dark Triad traits (i.e., psychopathy, Machiavellianism, and narcissism) relate to two measures of individual differences in life history strategies. In Study 1 (N = 937), we replicated prior observed links between life history strategies, as measured by the Mini-K, and the Dark Triad traits using samples recruited from three countries. In Study 2 (N = 1032), we measured life history strategy using the Consideration of Future Consequences Scale and correlated it with the Dark Triad traits in samples recruited from three additional countries. While there was some variability across participant sex and country, the results were generally consistent in that psychopathy and (to a lesser extent) Machiavellianism were related to faster life history strategies and narcissism was related to slower life history strategies. These results add cross-cultural data and the use of two measures of life history speed to understand the Dark Triad traits from a life history perspective.